QSAR Modeling and Biological Testing of Some 15-LOX Inhibitors in a Series of Homo- and Heterocyclic Compounds - Veronika Khairullina; Yuliya Martynova; Matvey Kanevsky; Irina Kanevskaya; Yurii Zimin; Leonid Maksimov (Molecules)
This paper examines the quantitative structure–inhibitory activity relationship of 15-lipoxygenase (15-LOX) in sets of 100 homo- and heterocyclic compounds using GUSAR 2019 software. Statistically significant valid models were built to predict the IC50 parameter. A combination of MNA and QNA descriptors with three whole molecular descriptors (topological length, topological volume and lipophilicity) was used to develop 18 statistically significant, valid consensus QSAR models. These compounds showed varying degrees of inhibition of the catalytic activity of 15-LOX: the range of variation in the pIC50 value was 3.873. The satisfactory coincidence between the theoretically calculated and experimentally determined pIC50 values for compounds TS1, TS2 and 1–8 suggests the potential use of models M1–M18 for the virtual screening of virtual libraries and databases to find new potentially efficient inhibitors of 15-LOX.